Future perspectives on nonmedical prescribing. (June 2017) - Stewart, Derek; Jebara, Tesnime; Cunningham, Scott; Awaisu, Ahmed; Pallivalapila, Abdulrouf; MacLure, Katie
Many countries have implemented nonmedical prescribing (NMP) and many others are scoping prescribing practices with a view to developing NMP. This paper provides a future perspective on NMP in light of findings of an umbrella review of aspects of NMP. This is followed by coverage of the Scottish Government strategy of pharmacist prescribing and finally, consideration of two key challenges. The review identified seven systematic reviews of influences on prescribing decision-making, processes of prescribing, and barriers and facilitators to implementation. Decision making was reported as complex with many, and often conflicting, influences. Facilitators of NMP included perceived improved patient care and professional autonomy, while barriers included lack of defined roles and resource pressures. Three systematic reviews explored patient outcomes that were noted to be equivalent or better to physician prescribing. In particular, a Cochrane review of 46 studies of clinical, patient-reported, and resource-use outcomes of NMP compared with medical prescribing showed positive intervention-group effects. Despite positive findings, authors highlighted high bias, poor definition and description of 'prescribing' and the 'prescribing process' and difficulty in separating NMP effects from the contributions of other healthcare team members. While evidence of benefit and safety is essential to inform practice, for NMP to be implemented and sustained on a large scale, there needs to be clear commitment at the highest level. The approach being taken by the Scottish Government to pharmacist prescribing implementation may inform developments in other professions and countries. The vision is that by 2023, all pharmacists providing pharmaceutical care will be pharmacist-independent prescribers. There are, however, challenges to implementing NMP into working practice; two key challenges are the need for sustainable models of care and evaluation research. These challenges could be met by considering the theoretical basis for implementation, and robust and rigorous evaluation.